HEDONISTIC LIFESTYLE AND FINANCIAL DISTRESS: THE ROLE OF RELIGIOSITY - Shekarsari, Amanda Qomari; Padmantyo, Sri (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2023)
A teenager is someone who is in the transition period from child to adult. Many teenagers wrongly attribute it to their lack of knowledge in the field of finance. Teenagers often follow the times and impose lifestyles. A hedonic lifestyle can be defined as a lifestyle that values ​​pleasure. This kind of lifestyle requires a lot to remain a consumer. Therefore, teenagers need many boundaries, one of which is religious teachings or individual religiosity. This research is important because financial distress in teenagers can cause many negative things. This research aims to determine the effect of a hedonistic lifestyle on financial distress through another variable, namely religiosity. This research used a sample of 241 teenagers. The results of this research are that hedonism has a positive effect on financial distress, and religiosity increases the relationship between financial distress and hedonism. This research influences teenagers' lifestyles so they don't make mistakes in socializing. It is hoped that this research can be a guide for teenagers in managing their finances, especially in fulfilling their lifestyle. In future research, it is hoped that researchers will increase the number of samples and expand the research objects, they can choose research objects in Central Java or Indonesia. Researchers are aware of the limitations in data collection, it is hoped that future researchers can expand the research objects and subjects. The conclusion, the hedonistic lifestyle has a positive effect on financial distress and religiosity is able to moderate the influence of the hedonistic lifestyle on financial distress, namely weakening the relationship between the two.